Atrial fibrillation in patients treated with intravenous zoledronic or pamidronic acid: a pharmacoepidemiological study. Issue 3 (March 2021) - Pijnenburg, Luc; Salem, Joe-Elie; Lebrun-Vignes, Bénédicte; Sibilia, Jean; Javier, Rose-Marie; Arnaud, Laurent
Abstract : Objective: Atrial fibrillation (AF) may be triggered by intravenous bisphosphonates (IVBPs) such as zoledronic acid or pamidronic acid. Our objective was to confirm the association between AF and IVBPs in a real-life large pharmacovigilance database. Design: A systematic analysis of VigiBase, the World Health Organization's pharmacovigilance database. Methods: Analysis of adverse events reported as 'atrial fibrillation' (according to the Medical Dictionary for Drug Regulatory Activities) associated with the use of zoledronic acid or pamidronic acid, in VigiBase, the World Health Organization's global Individual Case Safety Report (ICSR) database. All ICSRs reporting AF associated with zoledronic acid or pamidronic acid were included in a disproportionality analysis determining the lower end of the 95% credibility interval for the information component (IC025 ), showing a statistical association when >0. Results: 530 ICSRs reporting on the association between AF and IVBPs were extracted. Bayesian disproportionality analysis detected a significant association between AF and use of zoledronic acid (IC025 = 1.83) and pamidronic acid (IC025 = 2.16). Further analysis of these ICSRs determined that AF was severe in 85.0% of cases and with a mortality of 17.7%. The risk of severe AF was increased (OR: 2.98 (95% CI: 1.17–7.57), P = 0.02) following zoledronic acid vs pamidronic acid, after adjustment for age and gender. Conclusions: This is the first VigiBase pharmacoepidemiological study confirming the association between IVBPs and AF. Most AF were severe, with a high frequency of lethal outcome. The risk of severe AF was increased following zoledronic acid use compared to pamidronic acid, advocating for a cautious use of IVBPs.